Anti-OSM Antibody Inhibits Tubulointerstitial Lesion in a Murine Model of Lupus Nephritis - Qingjuan Liu; Yunxia Du; Kejun Li; Wei Zhang; Xiaojuan Feng; Jun Hao; Hongbo Li; Shuxia Liu (Mediators of Inflammation)
The purpose of this study was to investigate the role of oncostatin M (OSM) in tubulointerstitial lesion (TIL) in lupus nephritis (LN). We found that OSM was highly expressed in the renal tissue of LN mice. OSM is one of the interleukin-6 cytokine family members. In order to clarify the role and mechanism of OSM in LN, mice with LN were treated with anti-OSM antibody or isotype antibody. We evaluated the tubular epithelial-mesenchymal transdifferentiation (EMT) by detecting the E-cadherin, α-smooth muscle actin (α-SMA), and fibronectin (FN) expression. We analyzed the inflammation by observing the monocyte chemotactic factor-1 (MCP-1) and intercellular adhesion molecule (ICAM-1) expression and calculated the tubulointerstitial fibrosis area by Masson staining. The results showed that anti-OSM antibody, rather than isotype antibody, improved EMT, inflammation, and tubulointerstitial fibrosis. In addition, the signal transducer and activator of transcription (STAT) 1 and STAT3 signaling was activated by tyrosine phosphorylation in LN mouse renal tissue, indicating that the phosphorylated STAT1 (p-STAT1) and p-STAT3 were involved in kidney injury. Moreover, decreased p-STAT3 instead of p-STAT1 has been observed after anti-OSM antibody injection. Thus, we concluded that OSM is associated with TIL in lupus nephritis, which may be connected with the activation of STAT3 rather than that of STAT1.